Um ensaio sobre identificação racial e de gênero na Escolas Públicas Brasileiras - Salvador, Pedro Ivo Camacho Alves (2010)
Using data from Brazil Test, 2007, we analyze the gain of note when the student has the same race and / or gender of the teacher, attributing this phenomenon the name of racial identification and / or gender. Using a multivariate linear model, combining as control variables in the profile of students, teachers, schools, and parents of students, given the limitations of the model used, the results indicate that there is an improvement in the identification statement. In a second step, we analyzed for each Brazilian state, I understand that everyone has their own circumstances in this matter, and found a relationship between quality education and the proportion of racial minorities as students against the coefficients of racial identification. Given such evidence, we conclude that gender identification showed significant, though low in magnitude, while the racial identification has a relatively high magnitude, and that goes toward reducing the gap between the scores of ethnic groups.